2008
DOI: 10.1111/j.1601-5223.1984.tb00919.x
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic lead exposure does not effect lymphocyte micronuclei in car radiator repair workers

Abstract: Eighteen individuals exposed to lead in their work with repair and reconditioning of car radiators were investigated regarding blood lead levels and frequencies of lymphocyte micronuclei. The micronuclei werc analyzed in cells with preserved cytoplasm. The lead-exposed group was compared with 12 white-collar workers with no occupational lead exposure. The mean blood lead levels were 2.3 (range 1.50-3.30) and 0.42 (range 0.20-1.05) Kmolil, respectively, with no overlapping of exposed subjects and controls. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 10 publications
(5 reference statements)
0
3
1
Order By: Relevance
“…Our findings are consistent with the above reports. However insignificant increase in MN in cultured peripheral blood lymphocytes of shipbreaking workers and car radiator repair workers was reported (Hoffmann et al 1984;O'Riordan and Evans 1974). Moreover, (Pelelova et al 1997) could not detect a significant increase in structural aberrations in 22 workers from a lead battery plant; the negative response observed in the above reports was in contrast to the positive data obtained in our study.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Our findings are consistent with the above reports. However insignificant increase in MN in cultured peripheral blood lymphocytes of shipbreaking workers and car radiator repair workers was reported (Hoffmann et al 1984;O'Riordan and Evans 1974). Moreover, (Pelelova et al 1997) could not detect a significant increase in structural aberrations in 22 workers from a lead battery plant; the negative response observed in the above reports was in contrast to the positive data obtained in our study.…”
Section: Discussioncontrasting
confidence: 86%
“…Presently, most of genotoxic studies on the effect of occupational lead exposure in humans are limited and controversial (Duydu et al 2001;Fracasso et al 2002;Hoffmann et al 1984;O'Riordan and Evans 1974). (Forni et al 1980) studied 18 females occupationally exposed to lead in the manufacture of storage batteries.…”
Section: Discussionmentioning
confidence: 99%
“…The vast majority of researchers have demonstrated an increase in MN rate in exposed individuals compared with control groups, consequently highlighting the possible role of MN assay as a stable indicator of chronic lead exposure [21,26,40,42,[47][48][49][50][51][52][53][54][55][56][57][58]. The only study that have not found any genotoxic effect using MN assay was that conducted by Hoffmann et al [59].…”
Section: Biomarkers Of Individual Susceptibility Single Nucleotide Pomentioning
confidence: 99%
“…They have investigated the effect of lead on the genetic material in a group of car repair and radiator reconditioning workers reporting an insignificant increase in MN in cultured peripheral blood lymphocytes of workers who were exposed to lead [59].…”
Section: Biomarkers Of Individual Susceptibility Single Nucleotide Pomentioning
confidence: 99%